Global changes threaten functional and taxonomic diversity of insular species worldwide - Leclerc, Camille; Villéger, Sébastien; Marino, Clara; Bellard, Céline (Diversity & distributions, 2020)
Aim The assessment of biodiversity patterns under global changes is currently biased towards taxonomic diversity, thus overlooking the ecological and functional aspects of species. Here, we characterized both taxonomic and functional diversity of insular biodiversity threatened by multiple threats. Location Worldwide islands (n = 4,348). Methods We analysed the relative importance of eleven major threats, including biological invasions or climate change, on 2,756 insular endemic mammals and birds. Species were functionally described using five ecological traits related to diet, habitat and body mass. We computed complementary taxonomic and functional diversity indices (richness, specialization, originality and vulnerability) of species pools affected by each threatening process to investigate relationships between diversity dimensions and threats. We also determined whether species‐specific traits are associated with specific threats. Results On average, 8% of insular endemic species at risk of extinction are impacted by threats, while 20% of their functional richness is affected. However, a marked disparity in functional richness values associated with each threat can be highlighted. In particular, cultivation and wildlife exploitation are the greatest threats to insular endemic species. Moreover, each threat may contribute to the loss of at least 10% of functional diversity, because it affects threatened species that support unique and extreme functions. Finally, we found complex patterns of species‐specific traits associated with particular threats that is not explain by the threatening processes (directly affecting survival or modifying habitat). For instance, cultivation threatens very large mammals, while urbanization threatens very small mammals. Main conclusions These findings reinforce the importance of exploring the vulnerability of biodiversity facets in the face of multiple threats. Anthropogenic pressures may result in a loss of unique functions within insular ecosystems, which provides important insights into the understanding of threatening processes at a global scale.